4-(Trimethylsilyl) Morpholine as a Multifunctional Electrolyte Additive in High Voltage Lithium Ion Batteries. Issue 7 (9th March 2020) - Yang, Jianzhong; Shkrob, Ilya; Liu, Kewei; Connell, Justin; Dietz Rago, Nancy L.; Zhang, Zhengcheng; Liao, Chen
Abstract : In this study we characterize 4-(trimethylsilyl) morpholine (TMSML ) as a multifunctional electrolyte additive in Li1.03 (Ni0.5 Mn0.3 Co0.2 )0.97 O2 (NMC532)//Graphite cells operating at 3–4.4 V. This additive completely prevents the hydrolysis of LiPF6 caused by traces of water in a carbonate electrolyte, both ex and in situ. It also inhibits oxidative decomposition of electrolyte on the energized cathode, impedes the formation of electrically insulating deposits on the cathode surface, decreases transition metal loss from the cathode in aged cells, improves the discharge capacity retention, and decreases the rise of cell resistance during aging. We trace these beneficial functions to the ease of nucleophilic substitution and the N–Si bond dissociation in the TMSML . Our results suggest that TMSML could be a promising electrolyte additive in the high voltage lithium ion batteries.